2006
DOI: 10.1017/cbo9780511755514
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Solids and Materials

Abstract: Mechanics of Solids and Materials intends to provide a modern and integrated treatment of the foundations of solid mechanics as applied to the mathematical description of material behavior. The 2006 book blends both innovative (large strain, strain rate, temperature, time dependent deformation and localized plastic deformation in crystalline solids, deformation of biological networks) and traditional (elastic theory of torsion, elastic beam and plate theories, contact mechanics) topics in a coherent theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(150 citation statements)
references
References 1 publication
3
143
0
4
Order By: Relevance
“…Detailed in-depth reviews of the crystal plasticity theory can be found in articles by Asaro [27,28] and Roters et al [29].…”
Section: Theorymentioning
confidence: 99%
“…Detailed in-depth reviews of the crystal plasticity theory can be found in articles by Asaro [27,28] and Roters et al [29].…”
Section: Theorymentioning
confidence: 99%
“…Physical properties are analyzed in three groups: mechanical properties, thermal properties, and electrochemical properties [1]. Measurements can be made by applying testing and standards at the nanoscale with mechanical properties such as macro, micro, and advanced technology [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The formulas are applied to calculate the elastic constants for a transversely isotropic monocrystalline zinc and an orthotropic human femural bone. Apart from the analytical point of view, the derived results may be of interest for the analysis of anisotropic elastic and inelastic material response (with an elastic component of strain or stress) in the mechanics of fiber reinforced composite materials [Hyer 1998;Vasiliev and Morozov 2001], creep mechanics [Drozdov 1998;Betten 2002], damage-elastoplasticity ], mechanics of brittle materials weakened by anisotropic crack distributions [Krajcinovic 1996;Voyiadjis and Kattan 1999], and biological materials (membranes or tissues) with embedded filament networks [Evans and Skalak 1980;Fung 1990;Humphrey 2002;Lubarda and Hoger 2002;Asaro and Lubarda 2006]. …”
Section: Resultsmentioning
confidence: 99%